A phenomenological study of business graduates' employment experiences in the changing economy - Throy Alexander Campbell (Journal for Labour Market Research, 2018)
This study explores the perspectives of business college graduates, how technology has shaped the structures of their jobs, and the role of non-technical skills as they navigate the changing career path. Three overlapping themes emerged from the data analysis: (1) influence of increased technology capabilities on job structures and careers; (2) participation in job-related training and formal education as means of adapting to the new work environment; and (3) the role of non-technical skills in the workplace amidst the intensification of technology change. This research provides higher education practitioners and labor market researchers qualitative perspectives on work structure changes.
Keywords: J21; J23; J40; J60; 330; Labor market; Career paths; Automation; Higher education